Islamic Values in Conservation Biology: Feasibility Analysis of a Religious-Integrated Textbook for Highered Biology Education - Angela, Lia (Pedagogi Hayati, 2024)
In the era of globalization, biology education faces challenges in integrating modern science with religious values, particularly in the context of conservation biology. The urgency of this research lies in the scarcity of formal biology education literature in Indonesia that incorporates Islamic principles, despite the potential of values such as khalifah fil ardh (stewardship of the earth) and tabdzir (prohibition of wastefulness) to provide ethical guidance for environmental preservation. This study aims to develop and validate a conservation biology textbook based on Islamic values for higher education using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The validation process involved five experts evaluating the content, language, presentation, and graphic aspects using a Likert-scale instrument. The results indicate that the textbook achieved a "highly valid" category, with average scores of 95.45% (content), 95.40% (language), 90.80% (presentation), and 90.50% (graphics). Experts provided valuable input for further refinement, including improving illustrations, enhancing conceptual interconnections, and adjusting advance organizers to increase learning engagement. These suggestions were incorporated into the final revision, making the textbook more effective in fostering holistic learning that integrates science and ethical values. This research recommends further studies to assess the effectiveness of the textbook in large-scale learning environments, the development of similar teaching materials for other disciplines, and the integration of more contextually relevant religious values into higher education to support the formation of ethically and scientifically literate generations.